Histology and Ultrastructure of Transitional Changes in Skin Morphology in the Juvenile and Adult Four-Striped Mouse (Rhabdomys pumilio) - Eranée Stewart; Moyosore Salihu Ajao; Amadi Ogonda Ihunwo (The Scientific World Journal)
The four-striped mouse has a grey to brown coloured coat with four characteristic dark stripes interspersed with three lighter stripes running along its back. The histological differences in the skin of the juvenile and adult mouse were investigated by Haematoxylin and Eosin and Masson Trichrome staining, while melanocytes in the skin were studied through melanin-specific Ferro-ferricyanide staining. The ultrastructure of the juvenile skin, hair follicles, and melanocytes was also explored. In both the juvenile and adult four-striped mouse, pigment-containing cells were observed in the dermis and were homogeneously dispersed throughout this layer. Apart from these cells, the histology of the skin of the adult four-striped mouse was similar to normal mammalian skin. In the juvenile four-striped mouse, abundant hair follicles of varying sizes were observed in the dermis and hypodermis, while hair follicles of similar size were only present in the dermis of adult four-striped mouse. Ultrastructural analysis of juvenile hair follicles revealed that the arrangement and differentiation of cellular layers were typical of a mammal. This study therefore provides unique transition pattern in the four-striped mouse skin morphology different from the textbook description of the normal mammalian skin.